Analisis Pemanfaatan Media Sosial Instagram dalam Strategi Pemasaran Produk Skincare Scarlett Whitening - Pudya Setia Wardana; Nazwar Priatama Budiansyah; Erwin Permana; Dian Riskarini (MANAJEMEN, 2026)
Instagram, as a social media platform, is utilized by the skincare brand Scarlett Whitening in this study to explore its marketing strategies. Secondary data are applied descriptively and qualitatively in this research. The findings indicate that Scarlett’s success in Indonesia’s beauty market is not solely attributed to its product quality but also to the significant impact of Instagram on its digital marketing efforts. The combination of engaging visual content, collaborations with influencers, interactive features, and the optimal use of Instagram Shop and Ads has enabled Scarlett to stand out among both local and international competitors. Through consistent and innovative digital marketing, Scarlett has established itself as a local brand with a strong and impressive image, ready to compete on the global stage. The study concludes that Instagram advertising strategies have effectively increased consumer engagement and strengthened Scarlett’s position within the beauty industry